Penerapan Metode Cerita Bergambar Untuk Meningkatkan Pemahaman Nilai-Nilai Kristiani Pada Siswa Kelas Iv Sd Negeri 078426 Sanawuyu Kabupaten Nias Utara (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2024)
This study aims to enhance the understanding of Christian values among 4th-grade students at SD Negeri 078426 Sanawuyu through the implementation of the picture story method. The method used in this research is Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. In Cycle I, the students showed a positive response to the picture stories but still relied on the teacher's explanation and were less independent in applying the values. In Cycle II, with an emphasis on group discussions and independent story creation, there was a significant improvement in students' understanding and independence. They were not only able to identify Christian values in the pictures but also developed stories and applied those values independently. The results of the study show that the picture story method, combined with interactive discussions, can enhance the understanding of Christian values and foster students' independence. In conclusion, the use of this method is effective in improving the quality of Christian Education learning in schools.